De la embriaguez, el amor y otros excesos : antropología de un proceso de patologización del sufrimiento (2017)
In this study, the author analyzes the rhetorics and practices of excess and moderation in the pathologization of addiction (in anthropology, this phenomenon is frequently attributed to medicalization/psychologization of social life, typical of early and late modernity). She defines 'addiction' as a kind of social suffering and proposes an analysis of a greater chronological depth to identify the historical-cultural forces of the phenomenon, which have served as conditions of possibility in their transition to become simultaneously disease and 'pathos' that demands to be cured. To achieve this goal, the author opted for a multisituated perspective, both on a space-time scale and in her interaction with some subjects and sources. In the first instance, she made an extensive critical review of secondary sources, which led to the genealogical and historical reconstruction of three conceptual domains: 1) melodrama as rhetoric of excess, 2) imagery about Hybris vs. Sophrosyne, and 3) the emergence...